A Restless Nature - Susan Byrne (Humanities)
During the Spanish Renaissance, curiosity was the catalyst for change and creativity. Earlier philosophical stories regarding the perils and pitfalls of curiosity, written by Plotinus and Hermes Trismegistus, were adapted to a quite positive end: human creativity in letters.